Advances in robot design and intelligent control: proceedings of the 25th Conference on Robotics in Alpe-Adria-Danube Region (RAAD16) - Rodić, Aleksandar; Borangiu, Theodor (Advances in intelligent systems and computing, 2017)
This book presents the proceedings of the 25th International Conference on Robotics in Alpe-Adria-Danube Region, RAAD 2016 held in Belgrade, Serbia, on June 30th-July 2nd, 2016. In keeping with the tradition of the event, RAAD 2016 covered all the important areas of research and innovation in new robot designs and intelligent robot control, with papers including Intelligent robot motion control; Robot vision and sensory processing; Novel design of robot manipulators and grippers; Robot applications in manufacturing and services; Autonomous systems, humanoid and walking robots; Human-robot interaction and collaboration; Cognitive robots and emotional intelligence; Medical, human-assistive robots and prosthetic design; Robots in construction and arts, and Evolution, education, legal and social issues of robotics. For the first time in RAAD history, the themes cloud robots, legal and ethical issues in robotics as well as robots in arts were included in the technical program. The book is a valuable resource for researchers in fields of robotics, engineers who implement robotic solutions in manufacturing, services and healthcare, and master’s and Ph.D. students working on robotics projects